DIALEKTIKA DALAM KOMPOSISI MUSIK LAMAK KATO LEGO BUNYI - MUHAMMAD HARIO EFENUR; Ediwar Ediwar; Muhammad Halim (Bercadik: Jurnal Pengkajian dan Penciptaan Seni, 2016)
ABSTRACT Lamak Kato-Lego Bunyi is a sentence found in Pasambahan, which in Indonesian means literally as beautiful word-clash of sound but the contextual meaning of this sentence is “the beauty of an agreement resulted from various opinions/inputs discussed previously”. The discussion refers to a democratic discussion, meaning everyone present has equal right to speak up his/her mind regardless what her/his age is. In this case, it carries the same idea with a Pasambahan.Pasambahan plays an important role in building Minangkabau people’s characters, a discussion room that has ethical, aesthetic, and educational values and teaches Minangkabau people how to convey polite/courteous words toward others. In the theory of conflict, discussion room has three elements or concepts in comprehending dialectics and several stages in completing the discussion. The elements found out in dialectics are thesis, antithesis and synthesis, and the stages in completing a discussion consist of the emergence of conflict, discussion, and agreement.The objective of this artwork is the Reinterpretation of Pasambahan. Several objects which become the inspiration and then are interpreted into this artwork consist of the room of democratic discussion, dialectics, and the positive value of Pasambahan which has good impacts on the supporting society. The embodiment of this artwork aims at being the medium of appreciation for artists and youths in noticing the importance of Pasambahan culture.